2015
DOI: 10.1021/acs.jpcc.5b01245
|View full text |Cite
|
Sign up to set email alerts
|

Spectroelectrochemical Study of the Photoinduced Catalytic Formation of 4,4′-Dimercaptoazobenzene from 4-Aminobenzenethiol Adsorbed on Nanostructured Copper

Abstract: 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 type and power density of the laser. SERS spectra showed the formation of the 4,4'-DMAB on the nanostructured Cu surface independently of the laser employed. For the sake of comparison SERS spectra of a self-assembled monolayer of the 4-ABT on Ag surfaces decorated with Ag nanostructu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 71 publications
(188 reference statements)
1
14
0
Order By: Relevance
“…For example, Xu and co-workers studied the electroreduction of CO 2 on Cu electrodes and reported that CO and H are able to co-adsorb at low overpotentials, but H can partially displace CO due to stronger Cu-H binding [144]. EC-SEIRAS has also found recent application in the study of photochemical reactions [147,148], electrochemical processes in ionic liquids [149,150], and a wide range of adsorption phenomena at metal electrodes [151][152][153][154][155][156][157]. Rodes et al monitored the adsorption of glycine on Au thin films using EC-SEIRAS and confirmed that the preferential binding mode is in a bidentate configuration (Figure 7(b)) and that co-adsorption of perchlorate anions from the electrolyte takes place [156].…”
Section: Electrochemical Infrared Spectroscopymentioning
confidence: 99%
“…For example, Xu and co-workers studied the electroreduction of CO 2 on Cu electrodes and reported that CO and H are able to co-adsorb at low overpotentials, but H can partially displace CO due to stronger Cu-H binding [144]. EC-SEIRAS has also found recent application in the study of photochemical reactions [147,148], electrochemical processes in ionic liquids [149,150], and a wide range of adsorption phenomena at metal electrodes [151][152][153][154][155][156][157]. Rodes et al monitored the adsorption of glycine on Au thin films using EC-SEIRAS and confirmed that the preferential binding mode is in a bidentate configuration (Figure 7(b)) and that co-adsorption of perchlorate anions from the electrolyte takes place [156].…”
Section: Electrochemical Infrared Spectroscopymentioning
confidence: 99%
“…Vidal-Iglesias [ 37 ], for example, made assignments of the calculated frequencies of monolayers of 4-aminobenzenethiol (4-ABT) on copper, based on the visualisation of the vibrational normal modes and the Surface-Enhanced Raman spectrum (SERS) using Molden. They write “Surface-enhanced raman scattering (SERS) spectra of self-assembled monolayers of 4 aminobenzenethiol (4-ABT) on copper (Cu) and silver (Ag) surfaces decorated with Cu and Ag nanostructures, respectively, have been obtained with lasers at 532, 632.8, 785, and 1064 nm.…”
Section: Resultsmentioning
confidence: 99%
“…SEC joins the best of electrochemistry and spectroscopy together during an electron‐transfer process. As can be inferred, this multiresponse and “teamwork” technique has been used in a large number of fields, including, for example, electron transfer processes , chemical reaction mechanisms , side reactions , electrocatalysis , corrosion , conducting polymers , solar cells , memory devices , supercapacitors , synthesis and characterization of nanoparticles , carbon nanomaterials , characterization of metal complexes , liquid/liquid interfaces , electrochromic materials or study of compounds of biological interest , among others.…”
Section: Whatmentioning
confidence: 99%